Effects of pain and pain management on motor recovery of spinal cord-injured patients: a longitudinal study - Cragg, Jacquelyn J.; Weidner, Norbert; Schuld, Christian (Neurorehabilitation and neural repair, 2016)
Background. Approximately 60% of patients suffering from acute spinal cord injury (SCI) develop pain within days to weeks after injury, which ultimately persists into chronic stages. To date, the consequences of pain after SCI have been largely examined in terms of interfering with quality of life. Objective. The objective of this study was to examine the effects of pain and pain management on neurological recovery after SCI. Methods. We analyzed clinical data in a prospective multicenter observational cohort study in patients with SCI. Using mixed effects regression techniques, total motor and sensory scores were modelled at 1, 3, 6, and 12 months postinjury. Results. A total of 225 individuals were included in the study (mean age: 45.8 ± 18 years, 80% male). At 1 month postinjury, 28% of individuals with SCI reported at- or below-level neuropathic pain. While pain classification showed no effect on neurological outcomes, individuals administered anticonvulsant medications at 1 month postinjury showed significant reductions in pain intensity (2 points over 1 year; P < .05) and greater recovery in total motor scores (7.3 points over 1 year; P < .05). This drug effect on motor recovery remained significant after adjustment for injury level and injury severity, pain classification, and pain intensity. Conclusion. While initial pain classification and intensity did not reveal an effect on motor recovery following acute SCI, anticonvulsants conferred a significant beneficial effect on motor outcomes. Early intervention with anticonvulsants may have effects beyond pain management and warrant further studies to evaluate the therapeutic effectiveness in human SCI.